Motives for Commencing Studies and Expectations Concerning Professional Competence in Students who Practice, Used to Practice or Have Never Practiced Sports - Leonard Nowak; Maria Alicja Nowak; Mariola Radzińska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
Aim: Economic development, connected with the concept of a society engaged in lifelong learning, demands that education produce optimal professional competences. The aim of this study was to determine the motives for the choice of physical education studies, and ascertain expectations concerning professional competences, as well as self-evaluation of competences acquired, in current and former athletes and non-athletes. Methods. 226 people were examined, all studying physical education at the Faculty of Physical Culture in Gorzow Wielkopolski, a branch of the University School of Physical Education in Poznan. Purposive sampling was used (Radzińska, Nowak, L., Nowak, M., 2013). The study included current (22.6%) and former athletes (31.8%) as well as non-athletes (45.6%). A diagnostic survey was employed, with the use of the techniques of auditorium questionnaire, interview and document analysis. In order to draw statistical conclusions, the trait frequency and the independence χ2 test were used. Results. Former athletes more often reported having been motivated to choose the studies by their interest in employment with institutions of physical culture while non-athletes by their wish to obtain jobs in schools (p ≤ 0.05). Expectations of competence in physical education methodology were indicated by all respondents, slightly more often by former athletes and non-athletes (p ≤ 0.05). For current athletes, competence in physical fitness was important. Psycho-pedagogical competence in motivating schoolchildren to work was expected by most students (84.5%), slightly more often by former athletes and non-athletes (p ≤ 0.05). Respondents rated their preparation for employment with regard to foreign languages and preparation for scientific work as average and fair, and their selfeducation ability and computer skills as good.